'Their Way of Punishing' Corporal Punishment by Indigenous Peoples and the Prohibition of Torture. Issue 4 (December 2015) - Dunkelberg, Alonso Gurmendi
Both the right of indigenous peoples to cultural integrity and the prohibition of torture and other cruel, inhuman and degrading treatments and punishments are vital features of the character of modern international law. However, these two essential components of modern international law do not always appear to see eye to eye with regards to corporal punishment as a criminal sanction in indigenous communities. Practices such as flogging and the stocks would normally be considered to fall within the torture spectrum or at least some kind of cruel, inhuman or degrading treatment or punishment under the various international instruments covering such crimes. However, notions of cultural integrity and identity cause uncertainty as to what status these practices should actually have in the context of indigenous peoples' rights. This article seeks to explain and offer a way to solve this disagreement. Specifically, while claiming that indigenous corporal punishment should be judged under the same standard as any other form of corporal punishment, it also proposes that, instead of a merely punitive approach, states should seek to establish transitional consultation processes under ILO Convention 169 to seek to discourage indigenous practices that breach international standards.